Comparison of Sequential and Concomitant Therapy for Eradication of Helicobacter Pylori - Faisal Shabbir; Shazia Nisar; Nadeem Ashraf; Babar Khan; Farzana Hakim; Hammad Khan (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the effectiveness of sequential and concomitant therapy for the eradication of Helicobacter pylori.